Dexamethasone Prophylaxis in Pediatric Open Heart Surgery Is Associated with Increased Blood Long Pentraxin PTX3: Potential Clinical Implications. (9th July 2011) - Lerzo, Franco; Peri, Giuseppe; Doni, Andrea; Bocca, Paola; Morandi, Fabio; Pistorio, Angela; Carleo, Anna Maria; Mantovani, Alberto; Pistoia, Vito; Prigione, Ignazia
Abstract : Glucocorticoid administration before cardiopulmonary bypass (CPB) can reduce the systemic inflammatory response and improve clinical outcome. Long pentraxin PTX3 is a novel inflammatory parameter that could play a protective cardiovascular role by regulating inflammation. Twenty-nine children undergoing open heart surgery were enrolled in the study. Fourteen received dexamethasone (1st dose 1.5 mg/Kg i.v. or i.m. the evening before surgery; 2nd dose 1.5 mg/kg i.v. before starting bypass) and fifteen children served as control. Blood PTX3, short pentraxin C-reactive protein (CRP), interleukin-1 receptor II (IL-1RII), fibrinogen and partial thromboplastin time (PTT) were assayed at different times. PTX3 levels significantly increased during CPB in dexamethasone-treated (+D) and dexamethasone-untreated (−D) subjects, but were significantly higher in +D than −D patients. CRP levels significantly increased both in +D and −D patients in the postoperative days, with values significantly higher in −D than +D patients. Fibrinogen and PTT values were significantly higher in −D than +D patients in the 1st postoperative day. IL-1RII plasma levels increased in the postoperative period in both groups. Dexamethasone prophylaxis in pediatric patients undergoing CPB for cardiac surgery is associated with a significant increase of blood PTX3 that could contribute to decreasing inflammatory parameters and improving patient clinical outcome.